Study on the mechanism of tungsten deuterium chemically assisted physical sputtering - Yi-Lang Mai; Xiao-Chun Li; Ya-Wen Li; Wei Wu; Zi-Qi Li; Qiang Qi; Fang Ding; Guang-Nan Luo; Hai-Shan Zhou (Nuclear Fusion)
Tungsten (W) is an ideal plasma-facing material (PFM) for fusion devices. Plasma irradiation induces W atoms sputtering, which negatively affects the confinement of core plasma and the operational lifespan of W PFM. Although physical sputtering of W has been extensively studied, recent experiments on TEXTOR, ASDEX, and EAST have observed a previously undetected phenomenon: tungsten deuterium (WD) chemically assisted physical sputtering. Although the mechanism of WD chemically assisted physical sputtering have been empirically identified, the ab initio description of the underlying processes is still uncertain. In this study, we focus on why WD co-sputtering occurs and what are the conditions that lead to WD co-sputtering. Ab initio molecular dynamics (AIMD) and bond order calculations reveal that WD co-sputtering is driven by the interatomic attraction between W and D. Bond order and binding energy trends show that as the sputtered W atom ascends from surface, electrons transfer from the W–surface to the W–D bond, strengthening the W–D binding energy. Ultimately, the W–D binding energy surpasses the D–surface binding energy, enabling WD co-sputtering. Molecular dynamics (MD) simulations considering practical conditions such as atomic momentum transfer, thermal perturbation, and varied sputtering directions further validated these findings. Combining multiscale simulations, this study provides a comprehensive analysis from electronic interaction to atomic collisions, ultimately uncovering the atomic scale mechanism of WD chemically assisted physical sputtering.